Modern Hijab fashion in Malaysia / Faeez Nur Samsudin - Samsudin, Faeez Nur (2013)
Hijab is a veil which covers the head which particularly worn by Muslim women. Muslim women most often wear it as a symbol of modesty, privacy, and morality. Each country has different way in wear a hijab and the different legal and cultural statuses in various countries. In several of countries, they also have different terms of hijab itself. Some of the countries stated hijab as chador in Persian, jilbab in Arab, burqa in Afganistan, tudung or veil in Malaysia and so on. As now hijab fashion nowadays has so many style and design, it is actually influence the cultural in a way of wearing a hijab. In some countries, there is no law that required women to cover their head, no limit that has set for women on how is exactly the way they should wear a hijab. When there is no limit that stated in is how exactly a hijab should wear, people getting obsessed to get a hijab into a fashion world. There are so many pattern of garment designed to satisfied everybody own materialistic needs.